F Formulasi Dan Uji Stabilitas Fisik Body Wash Ekstrak Etanol 70% Bunga Telang (Clitoria ternatea L.): Formulasi Dan Uji Stabilitas Fisik Body Wash Ekstrak Etanol 70% Bunga Telang (Clitoria ternatea L.) - Haikal, Vikri; Audina, Mia; Hidayah, Nur; Budi, Setia (LPPM Universitas Sari Mulia, 2023)
ABSTRACT Background: Body wash is made by adding antibacterial active ingredients to suppress the growth of microorganisms. Antibacterial metabolite compounds owned by 70% ethanol extract of butterfly pea flowers are saponins, tannins, terpenoids, alkaloids and flavonoids Objective: Knowing the effect of differences in natrosol concentrations of 0.5%, 1% and 1.5% on the stability of body wash formulations of butterfly pea flowers Methods: The research method used is quasy-experimental with a one-group pretest-posttest design Results: The organoleptical stability of the three stable formulas is consistent and has a purplish-blue color, the characteristic smell of falcon flowers. All three stable formulas are homogeneous. The high stability of foam and viscosity of the three formulas are stable and qualified. The pH stability of all three formulas meets the qualifying range. Conclusion: Variations in natrosol concentration affect the stability test of pH evaluation and have no effect on organoleptis stability tests, homogeneity, foam height, viscosity and emulsion type. The most optimal formulation is formulation II (1%)